Tubercular Tenosynovitis of Extensor Tendon of Ankle: An Incidental Finding of a Rare Case - Pandey, Bikash; Pant, Pujan; Bist, Aayush; Pandey, Nishant (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND Tuberculosis (TB) remains a significant global health issue, with both pulmonary and extrapulmonary forms. This report highlights a rare case of tuberculous tenosynovitis affecting the extensor tendons of the ankle in a 13-year-old boy who presented with progressively painful swelling following contact with a neighbour suffering from pulmonary TB. Initial assessments, including ultrasound, suggested a ganglionic cyst. Multiple rice bodies were discovered during surgical excision, and histopathology confirmed the diagnosis of tuberculous tenosynovitis. The patient was treated with antitubercular therapy for nine months, resulting in complete recovery without recurrence at a one-year follow-up. This case emphasizes the importance of considering TB in differential diagnoses of atypical musculoskeletal presentations, particularly in endemic regions like Nepal.